2013
DOI: 10.1017/s1355617713000465
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sleep Difficulties after Moderate–Severe Traumatic Brain Injury

Abstract: The objective of this study is to systematically investigate sleep following moderate-severe pediatric traumatic brain injury (TBI). School-aged children with moderate-severe TBI identified via hospital records were invited to participate, along with a school-age sibling. Subjective reports and objective actigraphy correlates of sleep were recorded: Children's Sleep Habits Questionnaire (CSHQ), Sleep Self-Report questionnaire (SSR), and 5-night actigraphy. TBI participants There was no evidence of circadian rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
(46 reference statements)
2
31
0
Order By: Relevance
“…However, sleep disturbances were common post-injury and included excessive daytime sleepiness, increased sleep latency and circadian rhythm disruption, though the latter was not as common (Gagner et al 2015). One such prospective study of 15 patients demonstrated that sleep onset and maintenance difficulties were significantly increased in the TBI group when compared to their siblings (Sumpter et al 2013). A similar recent prospective study evaluated 100 adolescent patients three to twelve months following TBI for sleep disturbances using questionnaires and actigraphy (Tham et al 2015).…”
Section: Special Considerations In the Pediatric Populationmentioning
confidence: 99%
“…However, sleep disturbances were common post-injury and included excessive daytime sleepiness, increased sleep latency and circadian rhythm disruption, though the latter was not as common (Gagner et al 2015). One such prospective study of 15 patients demonstrated that sleep onset and maintenance difficulties were significantly increased in the TBI group when compared to their siblings (Sumpter et al 2013). A similar recent prospective study evaluated 100 adolescent patients three to twelve months following TBI for sleep disturbances using questionnaires and actigraphy (Tham et al 2015).…”
Section: Special Considerations In the Pediatric Populationmentioning
confidence: 99%
“…Several studies have shown more sleep disturbance in children with TBI than in healthy children or in those with orthopedic injuries (OIs). [6][7][8][9][10] Sleep problems have been demonstrated in children with both mild (mTBI) and more severe TBI (sTBI), persisting up to 3 years postinjury, as measured by self-and parent ratings as well as by objective sleep-monitoring measures (e.g., actigraphy and polysomnography [PSG]). 7,10 However, not all studies have found sleep problems to be associated with TBI or to be related to injury severity.…”
Section: Introductionmentioning
confidence: 99%
“…The short-term and long-term consequences of brain injury o en include disrup on of the day/night rhythm [255,256]. The expression of Bmal1 and Cry1 is deregulated in mice with trauma c brain injury [257].…”
Section: Genotype-phenotype Correlations For Mutations and Polymorphimentioning
confidence: 99%